Deadwood : la naissance d’une ville - Nathalie Massip (Anglophonia)
Broadcast on H.Β.Ο. from 2004 to 2006, Deadwood is an American western television series that depicts the construction and transformation of a miners’ camp into a booming town in South Dakota in the 1870s. Being in Indian territory, the camp is not part of the U.S.A., and there is no law but the law of the strongest. Yet, its inhabitants soon realize that they need to curb some of their tendencies toward anarchy and savagery and embrace certain rudiments of civilized society for their survival. The arrival of the telegraph, the development of the press, and the opening of a bank, among other elements, are supposed to accompany the passage from anarchy to democracy, just as the establishment of an informal local government is meant to make the community lawful Discovering the ecology of this nascent community, the viewer learns as much from the margins as from the thoroughfare, both being crucial in the development of the camp, despite their conflicting statuses. Yet, ultimately, it becomes evident that change and progress are not wanted, in Deadwood, and the series, deviating from most of its genre’s predecessors, seems to blur the frontier between savagery and civilization, in an attempt to debunk America’s mythologized past.